The Material Film Costume: Encountering the Mink Dress of Lady in the Dark (Leisen, 1944). (10th November 2022) - Colpaert, Lisa
Abstract: Over the last three decades, the study of film costume design has become a burgeoning field that predominantly engaged with the cinematic costume and its relationship with the female spectator. As film scholars have seldom looked at or worked with the actual garments, little to no academic attention is spent on the knowledge, experience, and invisible work of the costume designers and executers working in this field. This article implements the research methodology of material culture analysis, established in the field of fashion studies, but neglected in the area of film costume design studies. By stepping into the physical world of costume objects, the material culture analysis allows us to look beyond film costumes as kinetic, immaterial film images, and enables us to elucidate the histories and esthetics of garments that were created for specific film performances. Through an archival encounter with an extant costume object, an understanding of the creative and collaborative work conducted in the wardrobe department is facilitated. The central case of this paper is the mink dress of Lady in the Dark, a lavish musical drama set in the fashion industry, and directed by Mitchell Leisen, who started his career as a costume designer.